Conceptualizing "Job Leadership in the Marketing Mix" for Success and Knowledge Transfer in Small Businesses Distant from Consumer Markets (Case Study: Employment Projects of Imam Khomeini Relief Foundation, Ilam Province) - Parsamehr, Ali Mohammad; Hassani, Seyed Reza; Namamian, Farshid; Bahmani, Parisa (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study was conducted to examine the conceptualization of "Job Leadership in the Marketing Mix" for success and knowledge transfer in small businesses distant from consumer markets (case study: employment projects of Imam Khomeini Relief Foundation, Ilam Province). Methodology: Data were collected through interviews with 13 managers, experts in the field of job leadership, and officials in the relevant domain at the Imam Khomeini Relief Foundation. In this study, participants were selected using two non-probability sampling methods: purposive (judgmental) sampling and snowball sampling. The data were analyzed through three stages of open, axial, and selective coding. During the three stages of coding, the primary and secondary categories of job leadership in the marketing mix were identified. Data analysis was performed using MAXQDA qualitative software. Findings: The findings of the study (165 initial codes or concepts, 115 subcategories, and 22 main categories) included presenting a model comprising causal, contextual, and intervening conditions, introducing the central phenomenon, presenting strategies for job leadership in the marketing mix, and identifying its outcomes. Conclusion: The results indicate that conceptualizing "Job Leadership in the Marketing Mix" in the employment projects of the Relief Foundation has certain outcomes, including improving the welfare and livelihoods of households, strengthening family foundations, and enhancing skill training and empowerment.